Hyperreactio Luteinalis Associated with Pregnancy: A Case Report and Review of the Literature - Schnorr, John A., Jr.; Miller, Hugh; Davis, John R.; Hatch, Kenneth; Seeds, John (American Journal of Perinatology, 1996)
Hyperreactio luteinalis is a condition associated with bilateral and, in rare cases, unilateral ovarian enlargement due to theca lutein cysts. Hyperreactio luteinalis is a benign condition, usually found incidentally at cesarean section, which can appear anaplastic and lead to unnecessary ovarian resection. A 21-year-old Hispanic woman, G2P1, presented at 19 weeks with a singleton pregnancy, bilaterally enlarged ovaries, and a normal βhCG. Over the next four months, her ovaries increased 75% in size with the right ovary becoming entrapped in the pelvis. The patient underwent a primary low transverse cesarean section. The ovaries had an anaplastic appearance and on frozen section revealed multiple benign theca lutein cysts. There are 51 reported cases of hyperreactio luteinalis associated with a normal pregnancy in the literature. It is estimated that approximately 60% of the cases of hyperreactio luteinalis unassociated with trophoblastic disease occur with normal singleton pregnancy. There are multiple benign ovarian lesions including hyperreactio luteinalis that can mimic ovarian neoplasms. Accordingly, it is important to exclude these from the differential diagnosis via a wedge biopsy and frozen section to avoid unnecessary surgical excision.
Keywords: Hyperreactio luteinalis; ovarian neoplasm; ovarian enlargement; theca lutein cysts